2021
DOI: 10.1093/mnras/stab432
|View full text |Cite
|
Sign up to set email alerts
|

MMT spectroscopy of Lyman-alpha at z ≃ 7: evidence for accelerated reionization around massive galaxies

Abstract: Reionization-era galaxies tend to exhibit weak Lyα emission, likely reflecting attenuation from an increasingly neutral IGM. Recent observations have begun to reveal exceptions to this picture, with strong Lyα emission now known in four of the most massive z=7–9 galaxies in the CANDELS fields, all of which also exhibit intense [OIII]+Hβ emission (EW>800 Å). To better understand why Lyα is anomalously strong in a subset of massive z ≃ 7 − 9 galaxies, we have initiated an MMT/Binospec survey targeting a l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
100
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(126 citation statements)
references
References 169 publications
(287 reference statements)
26
100
0
Order By: Relevance
“…This is explained as UV bright galaxies are likely located in highly ionized bubbles which were created by a wealth of ionizing photons produced by those galaxies as well as a potentially larger number of nearby fainter galaxies (Finkelstein et al 2019b, Larson et al 2021. Endsley et al (2021a) provide additional evidence for accelerated reionization around massive galaxies. Particularly, they find a higher Lyα detection rate at z 7 from massive galaxies with strong [O III]+Hβ emission, which reflects enhanced ionizing photo production rates (e.g., Roberts-Borsani et al 2016;Tang et al 2019Tang et al , 2021aEndsley et al 2021b), arguing for higher Lyα equivalentwidths (EWs) from the strong [O III]+Hβ emitting population as similar as shown at lower redshifts of z 2 -3 (Tang et al 2021b).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…This is explained as UV bright galaxies are likely located in highly ionized bubbles which were created by a wealth of ionizing photons produced by those galaxies as well as a potentially larger number of nearby fainter galaxies (Finkelstein et al 2019b, Larson et al 2021. Endsley et al (2021a) provide additional evidence for accelerated reionization around massive galaxies. Particularly, they find a higher Lyα detection rate at z 7 from massive galaxies with strong [O III]+Hβ emission, which reflects enhanced ionizing photo production rates (e.g., Roberts-Borsani et al 2016;Tang et al 2019Tang et al , 2021aEndsley et al 2021b), arguing for higher Lyα equivalentwidths (EWs) from the strong [O III]+Hβ emitting population as similar as shown at lower redshifts of z 2 -3 (Tang et al 2021b).…”
Section: Introductionmentioning
confidence: 70%
“…These UV bright galaxies are likely to be centered in overdense regions where they cluster with fainter galaxies (and these may be beyond current detection limits). The combination of ionizing photons from the galaxies in the overdense regions may provide significant ionizing photon budget around UV bright galaxies (Finkelstein et al 2019b;Endsley et al 2021a, Larson et al 2021. In contrast, UV-fainter galaxies have more neutral gas around them (i.e., they sit in smaller ionized bubbles), thus the Lyα transmission to the IGM is suppressed.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EELGs are easy to identify in grism observations (Atek et al 2011;Maseda et al 2018;Boyett et al 2021), which have confirmed a steep positive evolution in their number density from the local value to higher redshifts (Noeske et al 2006). More recent studies have used slit-based spectroscopy to push these measurements to redshift z ≈ 7 and beyond (Endsley et al 2021). The upcoming Near-Infrared (NIR) grism missions Euclid and the Nancy Grace Roman Space Telescope (RST ) should detect the full population of these galaxies selected by Hα emission at 0.7 < z < 2.05 and by [OIII]λ5007 emission at 1.2 < z < 3 over tens of thousands of square degrees.…”
Section: Introductionmentioning
confidence: 99%
“…These studies yield a drop in the fraction of Ly α emitting galaxies at z > 6 (e.g. [10][11][12][13][14][15][16][17][18][19][20][21][22][23]), although there exist exceptions such as in observations of UV-faint galaxies behind galaxy cluster lenses [24], massive galaxies [25], and possibly in cases of ionised bubbles around bright galaxies [26]. There is also some evidence for a late reionization scenario (e.g.…”
Section: Introductionmentioning
confidence: 99%